The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1080/23273798.2019.1599129
|View full text |Cite
|
Sign up to set email alerts
|

Processing derived verbs: the role of motor-relatedness and type of morphological priming

Abstract: There is no consensus on whether derived words are decomposed or processed holistically, and on which factors this depends. Using overt visual priming with lexical decision involving Dutch derived particle verbs, we manipulated three factors: semantic transparency of the derived words, motorrelatedness of the simple verb constituent, and type of morphological priming. Experiments 1 and 2 (using simple verbs primed by their derivations or vice versa) showed overall facilitatory morphological priming effects, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 54 publications
2
8
3
Order By: Relevance
“…Experiments addressing speech production in Dutch (Roelofs, 1997a,b;Roelofs et al, 2002) likewise observed, using the implicit priming task, that priming effects were equivalent for transparent and opaque prime-target pairs. Morphological priming without effects of semantic transparency have recently been replicated in Dutch under overt prime presentations (Creemers et al, 2019;De Grauwe et al, 2019). Unprimed and primed visual lexical decision experiments on Dutch low-frequency suffixed words with high-frequency base words revealed that the semantics of opaque complex words were equally quickly available as the semantics of transparent complex words (Schreuder et al, 2003), contradicting the original prediction of this study that transparent words would show a processing advantage compared to their opaque counterparts.…”
Section: Introductioncontrasting
confidence: 88%
“…Experiments addressing speech production in Dutch (Roelofs, 1997a,b;Roelofs et al, 2002) likewise observed, using the implicit priming task, that priming effects were equivalent for transparent and opaque prime-target pairs. Morphological priming without effects of semantic transparency have recently been replicated in Dutch under overt prime presentations (Creemers et al, 2019;De Grauwe et al, 2019). Unprimed and primed visual lexical decision experiments on Dutch low-frequency suffixed words with high-frequency base words revealed that the semantics of opaque complex words were equally quickly available as the semantics of transparent complex words (Schreuder et al, 2003), contradicting the original prediction of this study that transparent words would show a processing advantage compared to their opaque counterparts.…”
Section: Introductioncontrasting
confidence: 88%
“…This relates further to a large body of semantic priming literature that shows that priming effects increase in magnitude as the relatedness proportion increases (for an overview see Hutchison, 2007). Second, we included semantic associates that are nouns, as was done in De Grauwe et al (2019), such that critical prime-target pairs consisted not only of verb-verb pairs but also of verbnoun pairs. Finally, as noted above, we presented primes and targets auditorily, which has been shown to result in larger effect sizes for semantic and associative priming compared to visually presented stimuli (Gomes et al, 1997;Hutchison, 2003).…”
Section: The Present Studymentioning
confidence: 94%
“…umbringen "kill" → MORD "murder") also did not lead to significant priming effects in the shorter SOA experiment, while this condition did show significant priming in experiments with longer SOAs. Second, the designs in De Grauwe et al (2019) and Zwitserlood et al (2005) used between-target designs. The different priming patterns could thus, in principle, be due to differences between the individual targets in the different conditions.…”
Section: Semantic Stem Priming With Opaque Wordsmentioning
confidence: 99%
See 2 more Smart Citations